Acoustic localization of a buoyancy driven model using a beamforming hydrophone array. (March 2021) - Fischer, Jeoffrey; Doolan, Con; Rowan, Martin; Lamos, Daniel; Seers, Jeffrey; Vargas, Oscar; Lam, Stephen; Skvortsov, Alex
Highlights: A novel experimental set up using a buoyancy driven model and a circular acoustic array. A modification of the conventional beamforming algorithm to track a moving source. The model trajectories for different runs are consistent at mid-frequencies. Abstract: This paper presents a novel experimental method for the study of flow induced noise from underwater vehicles. Here, buoyancy driven models are combined with a hydrophone array in a large water tank. The advantage of the methodology is that the noise comes exclusively from the model. The data were processed using conventional beamforming in two configurations, by either using the whole signal or dividing it into several individual time segments, the so-called short-time beamforming method. The beamforming maps are accurate given the small number of sensors. The second method enabled to track the model location during its travel. The results for each test were consistent especially at high frequencies (from 2 kHz).